Utilizing multimedia technology to create educational tools for teaching national defense and security - Hung, Truong Quoc; Hoang, Vu Minh; Anh, Tran Thi Hai; Quang, Luong Phan; Lan, Nguyen Thi (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Fostering national defense and security knowledge is not merely a policy imperative but a fundamental necessity for our nation’s governance, crucial for reinforcing comprehensive national defense and ensuring the safety of our citizens. However, the traditional methods of imparting military expertise in high schools and universities face significant challenges, with outdated textbooks and static lectures often failing to engage students effectively. This article proposes a solution by advocating for the integration of multimedia technology into educational software, offering interactive simulations, virtual reality experiences, and multimedia presentations to bring national defense and security concepts to life. By embracing these innovative tools, we can enhance the quality of national defense and security instruction nationwide, engaging learners more effectively, fostering deeper comprehension, and ultimately strengthening our collective grasp of defense and security matters. By introducing multimedia technology into software development, this article aims to enhance the teaching of national defense and security to students across the country.